Pediatric Early Warning Score (PEWS) Application Compliance with Response Time and Patient Safety - Rusmawati, Aprin; Ellina, Agusta Dian; Fawzi, Alfian; Musa, Kamaru lImron (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Pediatric Early Warning Score (PEWS) is a scoring system for early detection or early warning to detect a worsening of the condition of pediatric patients. The purpose of this study was to determine the relationship between compliance with PEWS implementation with response time and patient safety at RSIA Muhammadiyah Probolinggo City. This research design uses correlation analytic with cross-sectional observation approach. The population in this study were all nurses at RSIA Muhammadiyah Probolinggo City. The sample in this study were 32 people. With the technique of probability sampling-random sampling. Data processing used chi square test. Compliance with PEWS implementation showed that most of them adhered to the application of PEWS as much as 25 (78%), response time obtained results that most were fast 25 (78%) and adhered to patient safety by 25 (78%). The analysis test uses the chi square test.